2010
DOI: 10.1080/10852351003640732
|View full text |Cite
|
Sign up to set email alerts
|

An Effective HIV Risk-Reduction Protocol for Drug-Using Female Sex Workers

Abstract: HIV prevention is an especially salient issue for women, given the ongoing feminization of the epidemic. Female sex workers are especially vulnerable to HIV infection, particularly those who are drug-using and engage in street-based sex exchange. This paper examines risk behaviors and HIV serostatus of 806 drug-using women sex workers in Miami, Florida, and assesses the relative impact of two HIV and hepatitis prevention interventions on changes in risk behavior. Drug-using sex workers were recruited using tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 16 publications
1
73
2
Order By: Relevance
“…Two of the included studies had longitudinal experimental designs intended to assess other outcomes [18, 33] and one was an observational cohort study [8]; from these, we collected baseline HIV prevalence data. We critically evaluated each included study to assess the likelihood that the prevalence estimates reported might be biased using the Joanna Briggs Institute critical appraisal tool for prevalence studies [34].…”
Section: Methodsmentioning
confidence: 99%
“…Two of the included studies had longitudinal experimental designs intended to assess other outcomes [18, 33] and one was an observational cohort study [8]; from these, we collected baseline HIV prevalence data. We critically evaluated each included study to assess the likelihood that the prevalence estimates reported might be biased using the Joanna Briggs Institute critical appraisal tool for prevalence studies [34].…”
Section: Methodsmentioning
confidence: 99%
“…For highly marginalized female sex workers, social support may be even more crucial for expressions of resilience. Findings from a risk reduction intervention study among street-based sex workers in Miami suggested that social support from peer counselors facilitated better engagement with and retention of the interventions (Surratt & Inciardi, 2010). Similar results were found among vulnerable sexual minority African American men (Buttram, Kurtz, & Surratt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach’s alpha of GVS in this sample was .717 and has been reported elsewhere as .86 (Titus, et al, 2003). Examples of questions include, “Has anyone ever hurt you by striking or beating you to the point that you had bruises, cuts, broken bones, or otherwise physically abused you?” and “Has anyone ever forced you to participated in sexual acts against your will, including a regular sexual partner, a family member, or friend?” Given the pervasive violence in the street-based sex work context (Kurtz et al, 2004; Surratt & Inciardi, 2010; Surratt et al, 2011), we chose to exclude the four “current worry” items in our instrumentation, as they were likely to be universally endorsed. As such, our GVS scale consists of 11 items in total.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…11 Behavioural effects of drug use or withdrawal symptoms may reduce ability to negotiate condom use or safe working location and increase risk-taking while working. 12 13 Injection drug use exposes street sex workers (SSWs) to risks of bloodborne virus infection, abscesses at injecting sites, deep vein thrombosis and septicaemia. 14 This is in addition to the health risks of street sex working which include genital infection, 15 bloodborne infection, 16 poor mental health, 17 18 exposure to violence 19 and an increased risk of death.…”
Section: Introductionmentioning
confidence: 99%